Venetoclax durable response in adult relapsed/refractory Philadelphia-negative acute lymphoblastic leukemia with JAK/STAT pathway alterations - Anna Ferrari; Delia Cangini; Andrea Ghelli Luserna di Rorà; Andrea Ghelli Luserna di Rorà; Annalisa Condorelli; Marta Pugliese; Giovanni Schininà; Sebastiano Cosentino; Eugenio Fonzi; Chiara Domizio; Giorgia Simonetti; Salvatore Leotta; et al. (Frontiers in Cell and Developmental Biology, 2023)
High-risk relapsed/refractory adult Philadelphia-negative (Ph−) B-cell acute lymphoblastic leukemia (B-ALL) is a great challenge due to limited possibilities to achieve and maintain a complete response. This also applies to cases with extramedullary (EM) involvement that have poor outcomes and no accepted standard therapeutic approaches. The incidence of EM localization in relapsed/refractory B-ALL is poorly investigated: data on patients treated with blinatumomab reported a 40% rate. Some responses were reported in EM patients with relapsed/refractory B-ALL treated with inotuzumab ozogamicin or CAR-T. However, molecular mechanisms of response or refractoriness are usually investigated neither at the medullary nor at EM sites. In the complex scenario of pluri-relapsed/refractory B-ALL patients, new target therapies are needed. Our analysis started with the case of an adult pluri-relapsed Ph− B-ALL patient, poorly sensitive to inotuzumab ozogamicin, donor lymphocyte infusions, and blinatumomab in EM disease, who achieved a durable/complete response after treatment with the BCL2-inhibitor venetoclax. The molecular characterization of medullary and EM samples revealed a tyrosine kinase domain JAK1 mutation in the bone marrow and EM samples at relapse. By comparing the expression level of BCL2- and JAK/STAT pathway-related genes between the patient samples, 136 adult JAK1wt B-ALL, and 15 healthy controls, we identified differentially expressed genes, including LIFR, MTOR, SOCS1/2, and BCL2/BCL2L1, that are variably modulated at diverse time points and might explain the prolonged response to venetoclax (particularly in the EM site, which was only partially affected by previous therapies). Our results suggest that the deep molecular characterization of both medullary and EM samples is fundamental to identifying effective and personalized targeted therapies.